Transposição do banco de sementes como estratégia de restauração ecológica para floresta estacional decidual, Santa Maria, RS - Piaia, Bruna Balestrin (2015)
The aim of this study was to test the transposition of the seed bank for ecological restoration of the Seasonal Deciduous Forest in Santa Maria, Rio Grande do Sul. Initially, we performed a preliminary analysis of the seed bank of three forest fragments in different stages of regeneration. In one of the fragments, the analysis was performed on the edge and center of the fragment to choose the donor sites for transposition. Thereafter, the seed bank of the center and edge of the forest fragment in medium stage regeneration (BSI and BSII) was transposed to two areas and deposited in 1m² plots. The plots were arranged in a completely randomized design with three treatments (BSI, BSII and control) and six replications. We collected data floristic composition, seedling emergence, density and mortality in each treatment and deposition area for twelve months. Repeated ANOVA measures were carried out in order to compare treatments for emergency, density, mortality and wealth seedlings. The Tukey test was used to compare treatments for the density and richness after twelve months of transposition. The floristic similarity between treatments and areas of deposition was evaluated based on cluster analysis. Results indicated that the composition of the regeneration from the seed bank transposed presented different lifeforms, basically formed by pioneer herbaceous species. Density was influenced by the winter period and local condition in relation to the characteristics of soil hydromorphy. A growing number of species was observed along the twelve months. The seed bank of both donor sites contributed to the inclusion of tree lifeforms in the two deposition areas as well as the enrichment of the species.